A Student Serang Regency General Election Commission Socialization Level of First-Time Voter Participation in the 2024 Legislative Election Case Study of the Serang Regency General Election Commission Office - Heni Hardiyanti; Sulkiah Hendrawati; Wahyudi Wahyudi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the form and implementation of outreach activities conducted by the Serang Regency General Elections Commission (KPU) in preparation for the 2024 Legislative Elections. The study uses a normative method combined with an empirical approach, including interviews with KPU officials and field data collection. The study focuses on the effectiveness of outreach strategies, both directly through the